Postoperative diaphragmatic hernia following endoscopic thoracic sympathectomy for primary palmar hyperhidrosis: A case report - Wang, Ling; Wu, Xike; Tang, Yuepu; Fan, Zheyuan (Frontiers in Surgery, 2023)
Postoperative diaphragmatic hernia (DH) following endoscopic thoracic sympathectomy for primary palmar hyperhidrosis is extremely rare. We present a 21-year-old female patient who developed a left DH with herniation of the stomach and gastric perforation on the first postoperative day after undergoing bilateral video-assisted thoracoscopic sympathectomy R4 ablation. She complained of severe dyspnea and chest pain, and emergency chest X-ray and computed tomography revealed left pleural effusion, collapse of the lung and left DH, which allowed the stomach to herniate into the chest. Emergency thoracoscopic surgery was performed. Intraoperatively, we repaired the diaphragmatic defect and replaced the stomach with the peritoneal cavity from the thoracic field. The patient was discharged without complications. She did not present with recurrent symptoms at the 3-month follow-up. Postoperative DH should be considered when patients complain of gastrointestinal or respiratory symptoms after sympathectomy, although it is very rare.